2009
DOI: 10.1073/pnas.0901229106
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of fast axonal transport is a pathogenic mechanism for intraneuronal amyloid beta

Abstract: The pathological mechanism by which A␤ causes neuronal dysfunction and death remains largely unknown. Deficiencies in fast axonal transport (FAT) were suggested to play a crucial role in neuronal dysfunction and loss for a diverse set of dying back neuropathologies including Alzheimer's disease (AD), but the molecular basis for pathological changes in FAT were undetermined. Recent findings indicate that soluble intracellular oligomeric A␤ (oA␤) species may play a critical role in AD pathology. Real-time analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
184
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(195 citation statements)
references
References 54 publications
11
184
0
Order By: Relevance
“…The progressive tubulin beading after oA␤ transfer shown here could be a sign of axonal disruption (Shah et al, 2009), indicating that oA␤ can cause axonal damage. Other researchers have proposed that axonal damage is part of the process that leads to neurodegeneration in AD (Pigino et al, 2009), and in concordance with this, a gradually increasing disruption of endosomes, a sign of cytotoxicity (Song et al, 2011), was also observed. This observation not only reinforces the role of intracellular A␤ in AD pathogenesis but also establishes the disease relevance associated with the cell-to-cell transfer of intracellular oA␤ .…”
Section: Discussionsupporting
confidence: 52%
“…The progressive tubulin beading after oA␤ transfer shown here could be a sign of axonal disruption (Shah et al, 2009), indicating that oA␤ can cause axonal damage. Other researchers have proposed that axonal damage is part of the process that leads to neurodegeneration in AD (Pigino et al, 2009), and in concordance with this, a gradually increasing disruption of endosomes, a sign of cytotoxicity (Song et al, 2011), was also observed. This observation not only reinforces the role of intracellular A␤ in AD pathogenesis but also establishes the disease relevance associated with the cell-to-cell transfer of intracellular oA␤ .…”
Section: Discussionsupporting
confidence: 52%
“…Because of their soluble characteristics and their ability to move freely within the neuropil, small oligomers and protofibrils can interfere with normal neuronal membrane function and have been demonstrated to hamper synaptic function 22,23 and to inhibit fast axonal transport. 24 They are also associated with memory deficits in animal models of AD. 48 These findings have led to the conclusion that soluble A␤ species may make a significant contribution to the earliest manifestations of cognitive deficits and dementia in man.…”
Section: A␤ Conformation and Neurotoxicitymentioning
confidence: 99%
“…21 Injections of plaque equivalent concentrations (200 pg) of fA␤ into the cerebral cortex of aged rhesus or mormoset monkeys produced significant neuronal loss and induced hyperphosphorylation of tau, both features of the AD brain. Recent in vitro evidence indicates that oA␤, which are believed to form before deposition of A␤ in plaques and are likely to interfere with synaptic function 22,23 and inhibit fast axonal transport, 24 may also lead to neuronal degeneration. [25][26][27][28] However, although there is abundant evidence demonstrating that oligomeric A␤ interferes with neuronal function, direct in vivo demonstration that this conformation of A␤ causes neuronal death is lacking.…”
mentioning
confidence: 99%
“…Aβ peptide has been shown to disrupt axonal transport in vitro [44]. Axonal transport is also compromised in aged brains [44]. Several lines of evidence investigating the link between axonal transport machinery and amyloid plaques suggested an involvement of anterograde transport rather than retrograde transport [45].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…APP is the precursor of Aβ peptide and is transported by fast axonal anterograde transport [43]. Aβ peptide has been shown to disrupt axonal transport in vitro [44]. Axonal transport is also compromised in aged brains [44].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%